Seismic Expression of Subsurface Structures in Potwar Plateau, Pakistan: A Multi-attribute Analysis Approach - Khan, Muhammad Younis; Awais, Muhammad (Indonesian Journal on Geoscience, 2025)
The Potwar Plateau in Himalayan fold-and-thrust belt is a major hydrocarbon producing region of Pakistan. The Eocene carbonates are predominantly known reservoirs in the plateau which are segmented due to faulting. This article main goal is to delineate faults and fractures by testing capabilities of three types of seismically derived attributes (geometrical, instantaneous, and wavelet). Potential of attributes was also exemplified by comparing results from seismic data sets of two fields with proven hydrocarbon potential in Potwar Plateau. Since fault and fracture information derived from a single seismic attribute is not accurate, a multi-attribute approach was adopted to discuss and to compare results of integrated attribute analysis technique for subsurface structural mapping of fault zones and throw distribution. Attribute anomalies on dip variance, trace and wavelet envelope maps identified as possible fault locations, were then analyzed on additional attribute (spectral decomposition) maps. Results indicate that some attributes could suppress surrounding noises and could visualize identified faults. The application of spectral decomposition shows more convincible results than other individual attributes. The added values of proposed methodology of multi-attribute analysis are validated through applications, including mapping qualitative aspects of throw along major thrusts, tracking horizontal strata on either side of deformed zones, faults detection offsetting reflectors at various scales, and delineating main subsurface geometry of pop-up structure. After subsurface mapping and digital extraction of fault information, current work highlight importance of implementation of these automated methods in seismic interpretation to aid in reservoir modelling techniques, especially in foreland areas with complex fault system (s), e.g. Potwar Plateau in Pakistani Himalaya.